Moesin integrates cortical and lamellar actin networks during Drosophila macrophage migration - Besaiz J. Sánchez-Sánchez; Stefania Marcotti; David Salvador-Garcia; María-del-Carmen Díaz-de-la-Loza; Mubarik Burki; Andrew J. Davidson; Will Wood; Brian M. Stramer (Nature Communications)
Abstract Cells are thought to adopt mechanistically distinct migration modes depending on cell-type and environmental factors. These modes are assumed to be driven by mutually exclusive actin cytoskeletal organizations, which are either lamellar (flat, branched network) or cortical (crosslinked to the plasma membrane). Here we exploit Drosophila macrophage (hemocyte) developmental dispersal to reveal that these cells maintain both a lamellar actin network at their cell front and a cortical actin network at the rear. Loss of classical actin cortex regulators, such as Moesin, perturb hemocyte morphology and cell migration. Furthermore, cortical and lamellipodial actin networks are interregulated. Upon phosphorylation and binding to the plasma membrane, Moesin is advected to the rear by lamellar actin flow. Simultaneously, the cortical actin network feeds back on the lamella to help regulate actin flow speed and leading-edge dynamics. These data reveal that hemocyte motility requires both lamellipodial and cortical actin architectures in homeostatic equilibrium.